Handbook of research on renewable energy and electric resources for sustainable rural development - Kharchenko, Valeriy 1938-; Vasant, Pandian 1961- (IGI Global, Disseminator of Knowledge, 2018)
"This book provides relevant information for representation of the wide public advanced achievements in the field of electrotechnologies, efficient use of electric resources and renewable energy sources which will be useful to a wide range of readers and doubtless positive impact on a solution of a problem of a sustainable development of new territories will make"...
Includes bibliographical references
Keywords: Renewable energy sources; Rural electrification; Rural development